2021
DOI: 10.5435/jaaosglobal-d-21-00027
|View full text |Cite
|
Sign up to set email alerts
|

Reporting and Analyzing Race and Ethnicity in Orthopaedic Clinical Trials: A Systematic Review

Abstract: Background: The distinction between race and ethnicity should be carefully understood and described for demographic data collection. Racial healthcare differences have been observed across many orthopaedic subspecialties. However, the frequency of reporting and analyzing race and ethnicity in orthopaedic clinical trials has not been determined. Therefore, the primary purpose of this systematic review was to determine how frequently race and ethnicity are reported and analyzed in orthopaedic clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 36 publications
4
26
0
Order By: Relevance
“…Despite rising awareness of orthopaedic healthcare disparities and efforts to mitigate differences in patient outcomes based on race and ethnicity, previous investigations of the orthopaedic evidence base have demonstrated limited diversity among study participants [40,47]. A systematic review of 158 United States orthopaedic randomized controlled trials (RCTs) that were published between 2008 and 2011 found that only 20.3% (32) of trials reported at least one race or ethnicity variable.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite rising awareness of orthopaedic healthcare disparities and efforts to mitigate differences in patient outcomes based on race and ethnicity, previous investigations of the orthopaedic evidence base have demonstrated limited diversity among study participants [40,47]. A systematic review of 158 United States orthopaedic randomized controlled trials (RCTs) that were published between 2008 and 2011 found that only 20.3% (32) of trials reported at least one race or ethnicity variable.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has suggested that a lack of minority representation in the orthopaedic evidence base may perpetuate disparities in metrics such as utilization [3,41], postoperative complications [7,20,38,48], and functional outcomes [21,27,44]. Likewise, others have suggested that increased reporting of racial and ethnic data may be an avenue to identify targets for policy intervention and to improve health equity [40,47]. Racial differences in tumor pathophysiology and the incidence of important genetic loci, for example, have been studied for soft tissue sarcomas and osteosarcomas [1,[33][34][35].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…PRO implementation in routine clinical care has been documented to have low adoption nationwide [ 13 ], which may further impede efforts to capture diverse populations. Additionally, reporting of certain factors such as race and ethnicity in clinical trials has not been widespread [ 14 ].…”
Section: Introductionmentioning
confidence: 99%